ELECTRICITY GENERATION FROM LANDFILL GAS - Budisulistiorini, Sri Hapsari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Energy  from  renewables  has  been  sought  to  replace  current  fossil  fuel  energy  generation. Landfill gas has great potential to generate power since it contains methane 40 to 60%. Utilizing an enhanced landfill  gas as fuel for  power generator is also  beneficial to reduce greenhouse gas  emission  from landfill  otherwise  it  will  escape  to  the  atmosphere.  Current  technology  in power  generation  from landfill  gas  includes  organic  rankine  cycle  (ORC)  and  stirling  cycle engine  (SCE)  to  add  the traditional  reciprocating  internal  combustion  engine  (ICE)  and  gas turbine  (GT).  The  state-of-the art  power  generation  technologies  have  been  developed  and demonstrated  in  the  US  whereas  in Australia,  landfill  gas  power  plant  remains  with  the conventional ones; reciprocating engine and gas turbine.